Impact of Small Scale Industries on Afghanistan's Economy - Abdin, Md. Shahnawaz; Sadid, Imam Ali (Journal of Commerce and Trade, 2018)
This study is based on secondary data was conducted to know the true impact of small scale industries on Afghanistan's economy. Throughout the history, especially in the era of Ghaznawian (10th – 12th centuries), the country witnessed great success in terms of industries e.g. in the areas of textiles, architectures, lithograph, tiles and so on. Till 2002 there were not much of development actions in terms of industries. As the study shows, it was only after 2002 that the government of Afghanistan made some special plans to develop industries. People started to work in small scale sectors like silk, felt, rug, wooden furniture etc. and create economic value for their country. Small scale industries contribute a lot to the economy of any country. It is a source of income and employment for people. The rural people are engaged with the sector and work independently. According to a survey, 70 per cent of the people consider the impact of the sector as positive, and more than 50 per cent say that the sector helps to eliminate poverty and bring economic development. The problems of lack of capital, infrastructure, organization, lack of skilled labor, security and strategic marketing are major impediments in the way of small scale industries in Afghanistan. Classification-JEL : L16, L26, O25, O53